(untitled) (Bioscience Journal, 2022)
The concentrations of nutrients in the leaves allow a better understanding of the nutritional status of oil palm plants, making it a tool for diagnosing the origins of nutritional problems and assisting in fertilizer recommendations. In this sense, the objective of the current research was to evaluate the leaf concentrations of N, P, K, Ca, Mg and S in the oil palm under fertilization with phosphate, potassium and magnesium in edaphoclimatic conditions of Eastern Amazon. The experiment was conducted at the AGROPALMA® Company in the municipality of Tailândia, state of Pará, Brazil. The experimental design used was randomized blocks in a factorial scheme 4 x 2 x 3 x 2, with four levels of phosphorus, two sources of phosphorus (natural phosphate and triple superphosphate), three levels of potassium and two levels of magnesium. Phosphorus fertilization increased the leaf concentrations of N, P, Ca and Mg, providing higher levels when triple superphosphate was applied. However, in adult oil palm plants (12 years old), there was different on leaf concentrations of N, P, K and S between phosphorus sources aphid. Potassium and magnesium fertilization only increased the leaf concentrations of K and Mg, respectively. Fertilization with P, K and Mg promotes adequate leaf concentrations of K, Ca, Mg e S in oil palm plants grown in the Eastern Amazon.